Smart battery management systems: towards an efficient integration of electrical energy storage in smart regions - Gano, António (2014)
Electrical energy storage systems for electric vehicles or stationary applications will be important actors in Smart Region's energy scenarios, strongly contributing to increase the efficient and sustainable use of available resources. However, massive integration of such systems stillposes many problems, requiring enhancements in batteries's life time, autonomy, reliability and cost. The development of new smart and accurate battery management systems able to communicate with a broad range of smart devices and energy management systems, to account with users' needs and smart management directives, are essential to operate such battery based energy storage systems, improving their overall performance. The paper discusses some of the technological developments needed in this domain and the requirements of smart battery management systems to comply with, presenting a modular hardward platform, developed at LNEG, as an example of required structure and functionalities, relevant both in electrical mobility and decentralized smart-grid energy storage systems.